Directional excitation of surface plasmon using multi-mode interference in an aperture - Alam, M. Z. (Sci Rep, 2021)
Plasmonics is a promising technology that can find many applications in nanophotonics and biosensing. Local excitation of surface plasmons with high directionality is required for many of these applications. We demonstrate that by controlling the interference of light in a metal slot with the adjustment of the angle of incidence, it is possible to achieve highly directional surface plasmon excitation. Our numerical analysis of the structure showing a strong directionality of excited surface plasmon is confirmed by near field scanning measurements. The proposed structure can be useful for many applications including excitation of plasmonic waveguides, nanolithography, and optical sensing. To illustrate its usefulness, we experimentally demonstrate that it can be used for highly directional excitation of a dielectric loaded plasmonic waveguide. We also propose a simple structure for surface plasmon interference lithography capable of providing high image contrast using this scheme.